Case Study of Zamboanga City (Forced Migration Area) - Ma. Luisa D. Barrios-Fabian (Philippine Institute for Development Studies (PIDS), 2004)
In the City of Zamboanga, the increase in growth rate during the first half of the decade (1990-1995) can be attributed to the net migration rate. This plus the rapid urbanization, has brought about positive and negative results, particularly on service delivery, resource mobilization and social concerns. Because rapid urbanization and the halaw problem in Zamboanga City has become a national and local concern, this study was initiated as part of the State of the Philippine Population Report of the Commission on Population. It will help local government officials to understand the critical role migration plays in shaping the socio-economic conditions especially of urban areas. There is a need to transform the negative effects of urbanization and migration through the conscious application of the population and development paradigm in the entire planning process at the various levels of governance. The consideration of the population characteristics will be an important determinant of the various social service requirements as well as the environmental needs. This will help ease the strain of the effects of rapid urbanization to the provision of basic services. It is important therefore to have adequate and updated data/information for proper planning and resource mobilization.
Keywords: 330; armed conflict; forced migration; halaws; evacuees; conflict-related displacement; Zamboanga City; Master Development Plan 1997-2012; Urbanisierung; Migrationspolitik; Philippinen; Wirkungsanalyse